Faculty perception of scholarly communication trends: usage and challenges of e-journals - Hussain , Abid; Baqi, Abdul (Journal of Quranic and Social Studies, 2022)
This study is an attempt to analyze the level of understanding and the perception of scholarly communication trends using e-journals by the faculty members and their possible challenges in the universities of the Balochistan. Being quantitative in nature this study used survey method as well as close ended questionnaires for collecting data from public sector universities of Balochistan. The findings of the study revealed that with the availability of limited resources the respondents have highly response on scholarly communication trends for e-journals. While this study confirms the role of scholarly communication trends, usage, perception and challenges towards e-journals of the public sector universities of the Balochistan, Pakistan. The results of this study make it obvious that the faculty members in these universities are aware about the importance of scholarly communication, their usage and upcoming challenges but still there is lack of orientation programs, electricity failure and the lack of budget for subscription to scholarly communication.